Application of team‐based learning for teaching food analysis. Issue 2 (15th April 2021) - Castro, Luis F.; Peuker, Steffen; Mott, Jennifer
Abstract: Food analysis courses introduce the theory and application of analytical procedures to characterize foods and their ingredients. Students learn the principles behind analytical techniques commonly used to analyze foods in the industry and evaluate their suitability for the analysis of specific food products. Food analysis courses have traditionally been taught in a lecture‐based format. The objective of this study was to evaluate the effectiveness of utilizing team‐based learning (TBL), an established collaborative learning technique, in an undergraduate food analysis course to enhance student learning. Post‐course student surveys, quizzes, and exam scores were used to assess the effectiveness of the TBL implementation. TBL uses pre‐reading assignments, individual and team quizzes, and problem solving in teams to create an active learning environment in the classroom that increases student engagement and long‐term learning. The results from surveys, quizzes, and exam scores from the Food Analysis course show a successful implementation in the classroom: no significant difference in the average midterm exam scores was observed between the TBL and lecture formats ( p ≤ 0.05), indicating that TBL maintained performance on midterm exams, students reported being engaged in the course, and the deliberately designed group work encouraged students to prepare for class and participate in the activities. The students also reported that they were able to recall information better, and that the effectiveness of TBL activities helped them strengthen concepts. In conclusion, the results suggest that TBL is beneficial for students in food analysis, and that implementation in additional food science courses could help improve student learning.